The Machinability Performance of RBD Palm Oil Dielectric Fluid on Electrical Discharge Machining (EDM) of AISI D2 Steel - Supawi, Aiman; Ahmad, Said; Ismail, Nur Ismaliza; Talib, Norfazillah; Lee , Woon Kiow; Abdul Haq, Reazul Haq; Haw, Ho Fu; Ibrahim, Mohd Rasidi; Karim, Fazida (International Journal of Integrated Engineering, 2022)
Electrical discharge machining (EDM) is a high-precision manufacturing process that may be implemented to any electrically conductive material, notwithstanding its of mechanical residences. It’s far a non-contact process using thermal energy that is used in a wide range of applications, especially for difficult-to-cut materials with complicated shapes and geometries. The dielectric is critical in this process as it focuses the plasma channel above the processing and also serves as a debris carrier. The long-term use of dielectric used in EDM process pollutes to the atmosphere and is harmful to the operator's health. This study compares the efficiency of refined, bleached, and deodorized (RBD) palm oil (cooking oil) with traditional hydrocarbon dielectric, kerosene using copper electrode in the finishing process of AISI D2 steel. Low peak current, Ip 1A to 5A and pulse duration, ton up to 150μs were chosen as the main parameters. The effects of material removal rate (MRR), electrode wear rate (EWR), and surface roughness (Ra) were evaluated. The result shows that RBD palm oil has higher MRR which is 33.4821mm3/min while kerosene is 22.4888mm3/min, both at Ip=5A and ton=150µs. The improvement when RBD palm oil is used as dielectric is 48.88% compared to kerosene. With the increase in peak current, the EWR increases but it is inversely proportional to the pulse duration. The lowest EWR is obtained at the same IP=1A and ton=150µs for both RBD palm oil and kerosene which is 0.0010mm3/min and 0.0002mm3/min respectively. The minimum value of Ra for RBD palm oil is 2.15µm at IP=1A and ton=150µs, while for kerosene it is 2.11µm at IP=1A and ton=150µs. In terms of finishing process efficiency, RBD palm oil, a biodegradable oil-based dielectric fluid, has shown significant potential in EDM processing of AISI D2 steel.